Innovation bundles dashboard for resilience and women empowerment - Puskur, Ranjitha; Nchanji, Eileen; Cosmas, Lutomia; Ketema, Dessalegn; Muteti, Thomas; Gartaula, Hom; Mukhopadhyay, Prama; Mapedza, Everisto D.; Chadha, Deepali (CGIAR System Organization, 2024)
Socio-technical innovation bundles dashboard designed to inform research on women empowerment and resilience.